The effect and application of section 8C in respect of the Private Equity Industry - Kay-Hards, James (Department of Finance and Tax, 2019)
Employers have used various means to remunerate, retain and incentivize employees. One of these methods, is through the allocation of ownership in the employer to the employee, which help align the financial interests of the company and the staff member. SARS and National Treasury regulate the taxation of these forms of remuneration, typically called employee share incentive schemes, through section 8C of the Income Tax Act. A common practice among these schemes, is for the employer to impose some form of restriction on the equity shares issued to the employee, usually limiting the holder’s ability to dispose of the instrument. Once an equity share with a restriction is issued to an employee by an employer – section 8C of the Act applies. These types of structures are prevalently in the private equity industry, but with a slight nuance: the employee will receive an equity share indirectly or directly linked to the private equity fund(s) operated by the private equity fund management company. This provides the staff member with ‘skin in the game’, ensuring the longevity of the private equity fund can be sustained, and provides a foundation on which a rapport can be built with investors. The underlying investments in the private equity fund will provide the value of the equity shares in question. In most cases, these amounts will be in capital in nature owing to the length of holding period and the intention with which those investments are acquired. However, the effect of section 8C is to classify the gains on the employees’ equity shares as income rather than capital. The private equity industry finds itself in a precarious position with respect to the long-term equity incentivisation of staff and aligning this with the long-term nature of the fund’s underlying investments.